CLINICAL EFFICIENCY OF THE USE OF LACTOGLOBULIN IN FREQUENCY DISEASING CHILDREN OF EARLY AGE - Sidikova Maryam Amankeldievna (Web of Journals Publishing, 2024)
Against the background of sporadic cases, outbreaks of infectious and toxic-infectious diseases caused by enteropathogenic Escherichia coli occur in children. The difficulties in treating these diseases are largely due to the lack of effective means of treatment and prevention [1,4,5,7,11,17]. Antibiotics often cause adverse reactions and complications, disturbances of the intestinal biocenosis. To date, a wide range of antibodies to various viruses and bacteria, a number of nonspecific protective factors, as well as neutrophils, lymphocytes, macrophages and factors that stimulate the growth of B. Bifida in the intestines of newborns have been found in human colostrum and milk [2,3,9,14,17,22].
Keywords: anticoliproteic lactoglobulin, coli infection, frequently ill young children.